Widening Income Distribution in Post-Handover Hong Kong. - Lui, Hon-Kwong (Taylor and Francis, 2013)
Before the handover to China in 1997, Hong Kong's economic growth was very strong and the unemployment rate dropped to a record low of 2.2 per cent. In recent years, the widening income dispersion in Hong Kong has caught public attention. This book investigates the economic development and changes in income distribution of Hong Kong from different perspectives. Based on latest empirical evidence of Hong Kong, the book examines the relationship between economic restructuring and rising income disparity. Public housing programmes in Hong Kong affect half of the population.